Electro-Osmotic Flow of Water–Methanol Mixtures Through Nafion Membranes Revisited: Composition and Temperature Dependence - Corti, Horacio R.; Trevani, Liliana (Frontiers in Energy Research, 2022)
The electro-osmotic drag coefficient of water and methanol mixtures through Nafion 117 membranes were measured as a function of the composition at several temperatures between 25 and 60 oC by using a two-compartment capillary cell with Ag/AgCl electrodes. The electro-osmotic water drag in HCl aqueous solutions is higher than that reported in measurements where the membrane is in contact with pure water; hence all the reported results were performed at the same acid concentration. It was found that the drag coefficient for pure methanol is about 40% higher than that for water at all the temperatures studied as a consequence of the expanded nanostructure of Nafion in methanol. The drag coefficients of the water-methanol mixtures exhibit a highly non-linearity, which can be explained by considering the Nafion sorption in the binary solvent. The electro-osmotic flow in pure methanol is similar to that of 5 M methanol aqueous solutions, which opens the opportunity to use pure methanol in DMFC. The methanol crossover due to permeability can be minimized. Controversial results with previous studies are also addressed